Handbook of Asian Management - Kwok Leung; White, Steven (Springer US, 2004)
Our understanding of management in Asia has not kept pace with the demands of managers and students. The Handbook of Asian Management provides in-depth critical reviews of central topics in strategy and organizational behavior research in Asian contexts. Leading scholars take stock of what has been learned and give clear directions towards greater rigor and relevance for research in this region